Sugars influence substrate temperature and larval growth in black soldier fly bioconversion - A. Fuhrmann; M. Gold; Y. Bi; P. Azzari; M.J. Zorrilla; N. Puniamoorthy; A. Mathys (Bioresource Technology Reports, 2026)

Micro- and nanoplastic size affects uptake and digestive tract region residence time in black soldier fly larvae during food waste bioconversion - Moritz Gold; Siebe Lievens; Jeroen De Smet; Daniela A. Peguero; Christelle Planche; Christopher Whitshaw; Andreas Scheidegger; Denise M. Mitrano; Alexander Mathys; Mik Van Der Borght (Waste Management, 2025)

Physical properties of food waste influence the efficiency of black soldier fly larvae bioconversion via microbial activity - A. Fuhrmann; M. Gold; R.K. Loh; C.X. Chu; I. Haberkorn; N. Puniamoorthy; A. Mathys (Journal of Environmental Management, 2025)

Subcutaneous zilucoplan: Evaluation of reproductive toxicology - Marie Lemper; C. Marc Luetjens; Antje Fuchs; Peter Hall; François-Xavier Mathy; Jeff Long; Joy Cavagnaro; Sucharita Roy; Evan A. Thackaberry; Petra Duda (Reproductive Toxicology, 2025)

Comprehensive industry-relevant black soldier fly bioconversion characterisation by a novel chamber system - A. Fuhrmann; M. Gold; L.H. Lau Heckmann; P. Pedersen; K. Shakhnovich; C.X. Chu; I. Haberkorn; N. Puniamoorthy; A. Mathys (Waste Management, 2025)

Preservation of agri-food byproducts by acidification and fermentation in black soldier fly larvae bioconversion - Giacomo Alciatore; Daniela A. Peguero; Moritz Gold; Christian Zurbrügg; Mutian Niu; Franco Bargetze; Alexander Mathys (Waste Management, 2024)

Productivity, amino acid profile, and protein bioaccessibility in heterotrophic batch cultivation of Galdieria sulphuraria - F. Abiusi; B. Tumulero; L. Neutsch; A. Mathys (Bioresource Technology, 2024)

Physical pretreatment of three biowastes to improve black soldier fly larvae bioconversion efficiency - Daniela A. Peguero; Moritz Gold; Laura Velasquez; Mutian Niu; Christian Zurbrügg; Alexander Mathys (Waste Management, 2024)

Low transfer of cadmium, lead and aflatoxin B1 to eggs and meat of laying hens receiving diets with black soldier fly larvae reared on contaminated substrates - M. Heuel; M. Kreuzer; I.D.M. Gangnat; E. Frossard; C. Zurbrügg; J. Egger; B. Dortmans; M. Gold; A. Mathys; J. Jaster-Keller; S. Weigel; C. Sandrock; et al. (Animal Feed Science and Technology, 2023)

Evaluation of ammonia pretreatment of four fibrous biowastes and its effect on black soldier fly larvae rearing performance - Daniela A. Peguero; Moritz Gold; Andrea Endara; Mutian Niu; Christian Zurbrügg; Alexander Mathys (Waste Management, 2023)

Damage Assessment of Supporting Pillars in an Underground Cave Using Joint Inversion of Electrical Resistivity and P-wave Velocity, Burgundy (France) - A. Carrier; P. Bottelin; L. Fabre; A. Mathy (Pure and Applied Geophysics, 2022)

CO2 embodied in trade: trends and fossil fuel drivers - Sylvain Weber; Reyer Gerlagh; Nicole A. Mathys; Daniel Moran (Environmental Science and Pollution Research, 2021)
The amount of CO 2 embodied in trade has substantially increased over the last decades. We contribute to understanding the reasons for this evolution by studying the trends and some drivers of the carbon intensity of trade over the period 1995–2009 in 41 countries and 35 sectors. Our empirical analysis relies on the World Input-Output Database (WIOD) to compute embodied carbon emissions. Our main findings are the following. First, average emission intensity of traded goods is higher than average emission intensity of final demand. Second, relatively “dirty” countries tend to specialize in emission-intensive sectors. Third, the share of goods produced in emission-intensive countries is rising. Finally, we find that coal abundance (measured as fuel rent and controlling for reverse causality) leads both to a specialization in “dirty” sectors and to an increase in emissions per output when controlling for sector structure, which amounts to a fossil fuel endowment effect. These findings suggest trade liberalization may increase global emissions and therefore highlight the importance of considering trade when designing CO 2 reduction strategies.

Seismic study of soda straws exposed to nearby blasting vibrations - P. Bottelin; L. Baillet; A. Mathy; L. Garnier; H. Cadet; O. Brenguier (Journal of Seismology, 2020)
This research study has been developed to preserve a remarkable soda straw population from vibrations emitted by nearby rock blasting. The Choranche stalactite cave (Vercors, France) contains thousands of exceptionally long soda straws reaching a few meters in length for ~ 0.5 cm in diameter. These slender speleothems are very vulnerable to vibrations not only because of their structural fragility but also because of their dynamic amplification. We found that soda straws’ first natural frequencies lie within the frequency range emitted by nearby rock blasting works (ten to hundreds of Hz). We used in situ blast records, laboratory characterization, and a dynamic 2D finite element code to simulate the load experienced by the soda straw population. We show that induced loads may be increased by a factor 5 due to resonance. Consequently, short soda straws (0.1–1 m) were found more vulnerable to nearby blasting vibrations than longer speleothems (> 1 m), despite greater own weight and inertial forces for the latter. Simulations made on several blast tests yielded an admissible 2.4 mm/s peak particle velocity along the cave. Subsequent blasting works were carried out in compliance with this threshold with no harm done to the soda straw population. We also computed the dynamic response of soda straws exposed to a regional earthquake. In this case, longer speleothems (> 1 m) are primarily affected by resonance because of ground motion lower frequency content. We show that the omission of dynamic resonance or its simplification as made in previous studies may significantly underestimate the induced load in speleothems.

LCA of mobility solutions: approaches and findings—66th LCA forum, Swiss Federal Institute of Technology, Zurich, 30 August, 2017 - Rolf Frischknecht; Christian Bauer; Andreas Froemelt; Stefanie Hellweg; Kirsten Biemann; Thomas Buetler; Brian Cox; Peter de Haan; Sebastian Hoerl; René Itten; Niels Jungbluth; Yorick Ligen; et al. (The International Journal of Life Cycle Assessment, 2018)

Tree biomass in the Swiss landscape: nationwide modelling for improved accounting for forest and non-forest trees - B. Price; A. Gomez; L. Mathys; O. Gardi; A. Schellenberger; C. Ginzler; E. Thürig (Environmental Monitoring and Assessment, 2017)

Rapid evolution of great kiskadees on Bermuda: an assessment of the ability of the island rule to predict the direction of contemporary evolution in exotic vertebrates - Blake A. Mathys; Julie L. Lockwood (Journal of Biogeography, 2009)
Aim To determine whether an exotic bird species, the great kiskadee ( Pitangus sulphuratus ), has diverged in morphology from its native source population, and, if so, has done so in a manner predicted by the island rule. The island rule predicts that insular vertebrates will tend towards dwarfism or gigantism when isolated on islands, depending on their body size. For birds, the island rule predicts that species with body sizes below 70–120 g should increase in size. The great kiskadee has a mean mass of c . 60 g in its native range, therefore we predicted that it would increase in size within the exotic, and more insular, Bermudan range. Location The islands of Bermuda (exotic population) and Trinidad (native source population). Methods We took eight morphological measurements on 84 individuals captured in the exotic (Bermudan) population and 62 individuals captured in the native source (Trinidadian) population. We compared morphological metrics between populations using univariate and principal components analyses. We assessed whether the effects of genetic drift could explain observed differences in morphology. We calculated divergence rates in haldanes and darwins for comparison with published examples of contemporary evolution. Finally, we used mark–recapture analysis to determine the effects of the measured morphological characters on survivorship within the exotic Bermudan population. Results Individuals in the exotic Bermudan population have larger morphological dimensions than individuals in the native source population on Trinidad. The degree of divergence in body mass (g) and bill width (mm) is probably not due to genetic drift. This rate of divergence is nearly equal to that observed amongst well‐documented examples of contemporary bird evolution, and is within the mid‐range of rates reported across taxa. There is no clear effect of body size on survivorship as only one character (bill width) was found to have an influence on individual survivorship. Main conclusions Exotic species provide useful systems for examining evolutionary predictions over contemporary time‐scales. We found that divergence between the exotic and native populations of this bird species occurred over c. 17 generations, and was in the direction predicted by the island rule, a principle based on the study of native species.

Tumor necrosis factor alpha leads to increased cell surface expression of CXCR4 in SK-N-MC cells - Kevin Rostasy; Gullue Gorgun; Yelena Kleyner; Anthony Garcia; Michael Kramer; Suzanne M Melanson; Jean Marie Mathys; Constantin Yiannoutsos; Paul R Skolnik; Bradford A Navia (Journal of NeuroVirology, 2005)

The influence of chronic inhibition of nitric oxide synthesis on contractile and relaxant properties of rat carotid and mesenteric arteries - Frank J. Heijenbrok; Marie-Jeanne Mathy; Martin Pfaffendorf; Pieter A. van Zwieten (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

β-Adrenergic responses are significantly enhanced in rat carotid artery with intimal hyperplasia - Frank J. Heijenbrok; Marie-Jeanne Mathy; Martin Pfaffendorf; Pieter A. van Zwieten (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Developments toward large-scale bacterial bioprocesses in the presence of bulk amounts of organic solvents - A. Schmid; A. Kollmer; R. G. Mathys; B. Witholt (Extremophiles, 1998)